Spiritually Integrated Cognitive Processing Therapy: A New Treatment for Post-traumatic Stress Disorder That Targets Moral Injury. Issue 1 (February 2018) - Pearce, Michelle; Haynes, Kerry; Rivera, Natalia R; Koenig, Harold G.
Background: Post-traumatic stress disorder (PTSD) is a debilitating disorder, and current treatments leave the majority of patients with unresolved symptoms. Moral injury (MI) may be one of the barriers that interfere with recovery from PTSD, particularly among current or former military service members. Objective: Given the psychological and spiritual aspects of MI, an intervention that addresses MI using spiritual resources in addition to psychological resources may be particularly effective in treating PTSD. To date, there are no existing empirically based individual treatments for PTSD and MI that make explicit use of a patient's spiritual resources, despite the evidence that spiritual beliefs/activities predict faster recovery from PTSD. Method: To address this gap, we adapted Cognitive Processing Therapy (CPT), an empirically validated treatment for PTSD, to integrate clients' spiritual beliefs, practices, values, and motivations. We call this treatment Spiritually Integrated CPT (SICPT). Results: This article describes this novel manualized therapeutic approach for treating MI in the setting of PTSD for spiritual/religious clients. We provide a description of SICPT and a brief summary of the 12 sessions. Then, we describe a case study in which the therapist helps a client use his spiritual resources to resolve MI and assist in the recovery from PTSD. Conclusion: SICPT may be a helpful way to reduce PTSD by targeting MI, addressing spiritual distress, and using a client's spiritual resources. In addition to the spiritual version (applicable for those of any religion and those who do not identify as religious), we have also developed 5 religion-specific manuals (Christianity, Judaism, Islam, Buddhism, and Hinduism) for clients who desire a more religion-specific approach.